Massage and Reiki used to reduce stress and anxiety: Randomized Clinical Trial - Leonice Fumiko Sato Kurebayashi; Ruth Natalia Teresa Turrini; Talita Pavarini Borges de Souza; Raymond Sehiji Takiguchi; Gisele Kuba; Marisa Toshi Nagumo
ABTRACT Objective: to evaluate the effectiveness of massage and reiki in the reduction of stress and anxiety in clients at the Institute for Integrated and Oriental Therapy in Sao Paulo (Brazil). Method: clinical tests randomly done in parallel with an initial sample of 122 people divided into three groups: Massage + Rest (G1), Massage + Reiki (G2) and a Control group without intervention (G3). The Stress Systems list and the Trace State Anxiety Inventory were used to evaluate the groups at the start and after 8 sessions (1 month), during 2015. Results: there were statistical differences (p = 0.000) according to the ANOVA (Analysis of Variance) for the stress amongst the groups 2 and 3 (p = 0.014) with a 33% reductions and a Cohen of 0.78. In relation to anxiety-state, there was a reduction in the intervention groups compared with the control group (p < 0.01) with a 21% reduction in group 2 (Cohen of 1.18) and a 16% reduction for group 1 (Cohen of 1.14). Conclusion: Massage + Reiki produced better results amongst the groups and the conclusion is for further studies to be done with the use of a placebo group to evaluate the impact of the technique separate from other techniques. RBR-42c8wp